Awareness, Attitude and Barriers Towards Evidence Based Dental Practice Amongst Practicing Dentists of Bhopal City - Manoj Gupta (Journal of Clinical and Diagnostic Research, 2015)
Introduction: Evidence based dental practice is said to be the recent best approach to provide treatments or interventions, methodically proven to be safe and sound, efficient and cost effective. So, for providing quality dental care, clinical expertise, research evidence and patient’s preferences all should be given equal importance. Aim: To assess the awareness, attitude & barriers of evidencebased dental practice (EBDP) amongst dentists of Bhopal city. Materials and Methods: The target population of this crosssectional study involves dentists of Bhopal city. Two hundred fifty private dentists of Bhopal were selected using convenience sampling technique. Data was collected using a self-administered questionnaire containing 15 questions for assessing Knowledge, attitude, practice & barriers in Evidence based practice. Chisquare, t-test & one-way ANOVA were applied for data analysis and p<0.05 was considered statistically significant. Results: The study revealed that dental practitioners had low knowledge about evidence based dental practices but they showed positive attitude towards adopting it in their future practice. There exist certain barriers in practice of evidence based dentistry. Conclusion: Including evidence based dental practice teaching in dental curriculum may prove to be a significant step in effective and efficient dental care delivery to the patients. Barriers in evidence based practice needs to be identified & eliminated.